2020
DOI: 10.3892/mmr.2020.11150
|View full text |Cite
|
Sign up to set email alerts
|

miR‑205 suppresses cell migration, invasion and EMT of colon cancer by targeting mouse double minute 4

Abstract: colon cancer is one of the most frequent malignant tumors, and microrna (mir)-205 is involved in the tumor progression. The present study aimed to explore the effects of mir-205 on human colon cancer and its targeting mechanism. The levels of mir-205 and mouse double minute 4 (MdM4) were determined via reverse transcription-quantitative (rT-q) Pcr and western blot analysis. a luciferase activity assay was performed to analyze the association between mir-205 and MdM4. cell viability, migration and invasion were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Notably, this miRNA has also reduced expressions of EMT markers including Snail-1, E-cadherin and VEGF as well as some other oncogenic proteins namely SMAD3 and AKT ( Mansoori et al, 2020 ). In this type of cancer, miR-145-5p, miR-383-5p, miR-3622a-3p, miR-205 and miR-200b inhibit EMT process through targeting CDCA3, SGK1, SALL4, MDM4 and HIF-1α, respectively ( Shang et al, 2017 ; Chong et al, 2019 ; Chang et al, 2020 ; Chen et al, 2020 ; Fan and Wang, 2020 ).…”
Section: Mirnas and Emtmentioning
confidence: 99%
“…Notably, this miRNA has also reduced expressions of EMT markers including Snail-1, E-cadherin and VEGF as well as some other oncogenic proteins namely SMAD3 and AKT ( Mansoori et al, 2020 ). In this type of cancer, miR-145-5p, miR-383-5p, miR-3622a-3p, miR-205 and miR-200b inhibit EMT process through targeting CDCA3, SGK1, SALL4, MDM4 and HIF-1α, respectively ( Shang et al, 2017 ; Chong et al, 2019 ; Chang et al, 2020 ; Chen et al, 2020 ; Fan and Wang, 2020 ).…”
Section: Mirnas and Emtmentioning
confidence: 99%
“…88,89 miR-200 has a recent role in inhibiting EMT. [90][91][92][93][94] In breast cancer, miRNA-221 and miRNA-222 are associated with EMT and metastasis. [95][96][97] Several studies have shown that miRNAs can suppress EMT by targeting the TFs involved in Wnt signalling or its downstream targets.…”
Section: Role Of Mirnas In Emtmentioning
confidence: 99%
“…miRNA‐194 involves multiple complex signalling pathways and MMP protein expression as well as EMT 88,89 . miR‐200 has a recent role in inhibiting EMT 90–94 . In breast cancer, miRNA‐221 and miRNA‐222 are associated with EMT and metastasis 95–97 .…”
Section: Role Of Mirnas In Emtmentioning
confidence: 99%
“…Advanced study demonstrated that overexpressed miR-25 inhibited proliferation, migration, and invasion of HCT116 cells. Additionally, the decreased N-cadherin, vimentin, MMP2, and MMP9 with the increase of E-cadherin were observed in miR-205-overexpressed cells [ 64 ]. MiR-145-5p were down-regulated in CRC samples and cell lines.…”
Section: Tsmirs In Emtmentioning
confidence: 99%